2021
DOI: 10.1002/chem.202005000
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Gold Nanoparticles and Infrared Radiation Enables Cytosolic Protein Delivery

Abstract: Cytosolic protein delivery remains elusive. The inability of most proteins to cross the cellular membrane is a huge hurdle. Here we explore the unique photothermal properties of gold nanorods (AuNRs) to trigger cytosolic delivery of proteins. Both partners, protein and AuNRs, are modified with a protease‐resistant cell‐penetrating peptide with nuclear targeting properties to induce internalization. Once internalized, spatiotemporal control of protein release is achieved by near‐infrared laser irradiation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…GNPs are attractive delivery vehicles due to their chemical inertness and excellent biocompatibility. The easy surface modification of GNPs, usually mediated through sulfur‐gold interactions, provides a flexible platform to deliver a broad range of therapeutic ingredients, including small organic molecules, 64 polymers, 65 and biomacromolecules such as proteins 66,67 and nucleic acids 68‐70 . These unique physiochemical and biological features make GNPs suitable for immune‐target delivery in a controlled‐release manner.…”
Section: Deliverymentioning
confidence: 99%
“…GNPs are attractive delivery vehicles due to their chemical inertness and excellent biocompatibility. The easy surface modification of GNPs, usually mediated through sulfur‐gold interactions, provides a flexible platform to deliver a broad range of therapeutic ingredients, including small organic molecules, 64 polymers, 65 and biomacromolecules such as proteins 66,67 and nucleic acids 68‐70 . These unique physiochemical and biological features make GNPs suitable for immune‐target delivery in a controlled‐release manner.…”
Section: Deliverymentioning
confidence: 99%
“…Therefore, we functionalized the BSA protein with r 8 to facilitate cell penetration of the AuNPs. Previous studies have shown that the use of arginine-rich CPPs increases cell penetration of the nanocarriers, opening the possibility for the improved cell internalization of AuNPs [ 51 , 57 , 58 , 59 ]. In particular, r 8 has been covalently linked to several molecules and nanosystems, such as insulin [ 60 ] liposomes, [ 61 ] quantum dots, [ 62 ] and gold nanorods, [ 49 , 58 ] improving their uptake and cell penetration in target sites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the use of arginine-rich CPPs increases cell penetration of the nanocarriers, opening the possibility for the improved cell internalization of AuNPs [ 51 , 57 , 58 , 59 ]. In particular, r 8 has been covalently linked to several molecules and nanosystems, such as insulin [ 60 ] liposomes, [ 61 ] quantum dots, [ 62 ] and gold nanorods, [ 49 , 58 ] improving their uptake and cell penetration in target sites. Nevertheless, coating AuNRs and AuNPrs (with absorption in the first biological window) with BSA, functionalized with r 8 for cell internalization, has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Highly stable AuNPs can be produced in different shapes and sizes, and they can be conjugated with different types of molecules, including drugs, proteins, nucleic acids, antibodies, enzymes and fluorescent dyes. Hence, AuNPs can be used for the targeted delivery of therapeutic agents such as drugs [4][5][6][7][8][9], proteins [10][11][12] and genes [13][14][15][16]. AuNPs possess unique electronic and optical properties, including the phenomenon of surface plasmon resonance (SPR) [17][18][19][20][21][22] which results from the interaction between an electromagnetic wave and conduction of electrons the metal.…”
Section: Introductionmentioning
confidence: 99%